Implementation of Tourism Development Policy Coronavirus Disease in Bali Province - Wahyu Sri Handono; Ida Ayu Putu Sri Widnyani; Nyoman Diah Utari Dewi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research aims to describe the Implementation of Bali Provincial Tourism Development Policy during the pandemic the 2019 CoronaVirus Disease; The obstacles faced and strategies to overcome the obstacles faced in the implementation of Regional Regulation No.5 of 2020 on Standards for The Implementation of Bali Cultural Tourism. The research methods used in this study are qualitatively descriptive. The results showed that (1) the implementation of tourism development policies in Bali province was influenced by (a) standards / sizes and policy objectives; (b) Resources; (c) the characteristics of the managing agent; (d) the attitude or tendency of the executors; (e) communication between organizations and implementing activities; and (f) Social, economic and political environment; (2) The obstacles faced in the implementation of tourism development policies in bali province also stem from factors (a) standards / size and policy objectives; (b) Resources; (c) the characteristics of the managing agent; (d) the attitude or tendency of the executors; (e) communication between organizations and implementing activities; and (f) Social, economic and political environment; currently the implementation of the policy is constrained by the pandemic the 2019 coronavirus disease; so that socialization has not been massive and the mandate of the regional regulation to form a regional public company has not been implemented, and the absence of tourists who come to Bali; (3) Strategies to deal with the obstacles faced in the implementation of tourism development policies in Bali province, especially those related to the pandemic the 2019 coronavirus; so that socialization has not been massive and the mandate of the regional regulation to form a regional public company has not been implemented, and the absence of tourists to Bali.